Exploring Pancasila Student Values In Efl Textbook Entitled English For Nusantara For Seventh Grade Students - Riani, Dinda; Utami, Praditya Putri (Peneliti.net, 2024)
The purpose of this research is to find out the values of Pancasila students and how these values are represented in the English for Nusantara textbook. This study uses a qualitative approach with content analysis method. The subjects in this study were pictures and conversation scripts in English for Nusantara textbooks. In obtaining data, the writer uses a checklist as an instrument. The author uses the values of the Pancasila student profile set by the Ministry of Education and Culture of the Republic of Indonesia, which forming a Pancasila student profile is one of the objectives of Merdeka curriculum. In the conversation script, 5 of 6 values are found, the values are represented explicitly through pictures by 95.35% and implicitly through elliciting conditions by 4.65%. Meanwhile in pictures, 6 of 6 values are found. The values represented explicitly through literal by 34.2% and implicitly through elliciting conditions by 57.9% and resultant actions by 7.9%. The results of this study are expected to be useful for teachers for determining learning sources, students, and further research.